Menjadi Perempuan di dalam Sinetron: Kekinian Femininitas - Widjajanti Mulyono – Santoso (Antropologi Indonesia, 2006)
The article depicts the representation of contemporary women in Indonesia using sinetron or soap opera. Representation of women has been in intrigue issue since in the New Order, women have been one of several important issues. Since the tumbling down of the New Order, market has been an important mechanism of dissemination of culture, and the representation of Indonesian women is one of the icon of the media. The most obvious visualization if women not only as victim of violence but also the doer of violence itself. Women is powerful, such representation is shown by widower, grown women toward powerless little girl. As such the sinetron is not a typical soap opera visualization that tends to visualizing romantic and sensual women. In general such representation is disadvantaging the position of women, as market becomes the powerful mechanism to disseminate such image. Women be cautious Keywords: Femininity, subordinate, culture, market.